2001
DOI: 10.1097/00003246-200110000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of normothermia versus hypothermia on extravascular lung water and serum cytokines during cardiopulmonary bypass: A randomized, controlled trial

Abstract: Normothermic CPB is not associated with additional inflammatory and related systemic adverse effects regarding cytokine production and EVLWI as compared with mild hypothermia. The potential temperature-dependent release of cytokines and subsequent inflammation has not been observed and normothermic CPB may be seen as a safe technique regarding this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 27 publications
4
19
1
2
Order By: Relevance
“…These results reinforce previous reports 2,3 . We also showed that peak levels of all cytokines occurred 4 h after the end of bypass, again concordant with other studies 3,5,6 . It is important to note that the groups in our study presented similar general characteristics, intraoperative parameters, and mortality rates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results reinforce previous reports 2,3 . We also showed that peak levels of all cytokines occurred 4 h after the end of bypass, again concordant with other studies 3,5,6 . It is important to note that the groups in our study presented similar general characteristics, intraoperative parameters, and mortality rates.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of perfusion temperature and cardioplegia type during bypass on the development of SIRS has been investigated previously, but results are unclear. Some reports did not find differences in serum cytokine levels between patients with normothermic and hypothermic bypass 5,14 , while others found a more rapid decline in IL-8 plasma levels in the former 6 . The use of blood cardioplegia, compared to crystalloid cardioplegia, has been mainly associated with increased myocardial protection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In an attempt to provide an estimate of pulmonary vascular permeability ratios of EVLW to TPTD derived blood volumes have been utilized. These ratios are intended to reflect EVLW in the context of, or indexed to preload, and were first described in 2001 by Honore et al 72 . The concept is intuitive; a high EVLW in a hypovolemic patient (and therefore an elevated ratio) would suggest capillary permeability is the primary pathology whilst low EVLW in a patient with elevated preload (and therefore a low ratio)…”
Section: Differentiating Hydrostatic Vs Permeability Pulmonary Edemamentioning
confidence: 99%
“…Мы не оп ределяли концентрацию провоспалительных и проти вовоспалительных цитокинов. Мы изучали влияние только умеренной гипотермии, которая наиболее широ ко используется в кардиохирургии [35]. Было показано, что глубокая гипотермия (28°C) не обладает преимуще ством перед умеренной гипотермией у пациентов при реваскуляризации миокарда в условиях искусственного кровообращения [36].…”
Section: рис 2 Roc кривая Ntprobnp как предиктор длительной гос питunclassified